Stress-strain state of the Heraklei volcano-tectonic block of the Mountainous Crimea - Murovskaya, A.V. (Geofizicheskiy Zhurnal, 2011)
This paper presents the paleostress results obtained for Heracleyskaya anticlinal (Western Crimea). On the basis of field tectonophysical study of brittle planes and 3D relief map deciphering the scheme of faults is made. Conjugate sets of fractures and fault-slip data are used to reconstruct orientation of the principal stress and deformation regimes. It is shown that the Heracleyskiy peninsula has been exposed to the 10 compression and tension deformation phases from the Middle Jurassic period. Stress reconstruction results are compared with gravitational field data. In the Neogen-Quaternary time for lower lithosphere the compression stress is characteristic while for upper crust the tension stress is typical as well. It seems to be connected with the recent raising of the Crimean mountains.